Intravenous thrombolysis with 0.65 mg/kg r-tPA may be optimal for Chinese mild-to-moderate stroke - Cui, Yu; Yao, Zhi-Guo; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background Intravenous recombinant tissue plasminogen activator (r-tPA) with 0.9 mg/kg is the standard treatment for acute ischemic stroke, but it remains unclear whether it is optimal for all patients. We aimed to determine the optimal dose of r-tPA for Chinese stroke based on the data from the INTRECIS study. Methods From the INTRECIS cohort, patients receiving intravenous r-tPA within 4.5 h of onset were included. According to r-tPA dose, patients were assigned into seven groups (from 0.60 to 0.90 mg/kg). The primary outcomes were the proportion of excellent functional outcomes and symptomatic intracranial hemorrhage. Results Overall, 2,666 patients were included: 156 in 0.60 mg/kg group, 117 in 0.65 mg/kg group, 127 in 0.70 mg/kg group, 188 in 0.75 mg/kg group, 154 in 0.80 mg/kg group, 359 in 0.85 mg/kg group, and 1,565 in 0.90 mg/kg group. After adjustment for baseline characteristics, only 0.65 mg/kg group had significantly higher proportion of excellent functional outcome than 0.90 mg/kg group (79.5 vs. 71.4%, odds ratio = 1.833, 95% CI = 1.006–3.341, adjusted p = 0.048). The subgroup analysis showed no evidence of differences in the odds of having a primary outcome between the two groups by age, admission NIHSS, onset to thrombolysis time, and TOAST classification. There was no significant difference in symptomatic intracranial hemorrhage between groups. Conclusion Our study presented the first evidence that intravenous thrombolysis with 0.65 mg/kg r-tPA may be optimal for Chinese mild-to-moderate stroke. Registration https://www.clinicaltrials.gov, identifier: NCT 02854592.